1)2 2/3÷2+(4/15+2/5)÷(3 1/3×3/5);
2 2/3:2=8/3×1/2=4/3=1 1/3
4/15+2/5=4/15+6/15=10/15=2/3
3 1/3×3/5=10/3×3/5=2
2/3:2=2/3×1/2=1/3
1 1/3+1/3=1 2/3
2)2÷1/4+((1 1/2+2 2/3)÷3 3/4-2/3)÷8 8/9;
2:1/4=2×4=8
1 1/2+2 2/3=3/2+8/3=9/6+16/6=25/6
25/6:3 3/4=25/6×4/15=10/9
10/9-2/3=10/9-6/9=4/9
4/9:8 8/9=4/9×9/80=1/20
8+1/20=8 1/20
3)(7/8-3/5)÷(2/3+1/2)×(60÷4 5/7);
7/8-3/5=35/40-24/40=11/40
2/3+1/2=4/6+3/6=7/6
60:4 5/7=60×7/33=420/33=140/11
11/40:7/6=11/40×6/7=33/140
33/140×140/11=3
4)(3 1/4+1 1/6÷1 5/9)÷2 2/7+5 1/9÷7 2/3
1 1/6:1 5/9=7/6×9/14=3/4
3 1/4+3/4=3 4/4=4
4:2 2/7=4×7/16=7/4
5 1/9:7 2/3=46/9×3/23=2/3
7/4+2/3=21/12+8/12=29/12=2 5/12
2 2/11 * x - 5/16 = 1 3/4
2 2/11 * x = 1 3/4 + 5/16
2 2/11 * x = 1 12/16 + 5/16
2 2/11 * x = 1 17/16
24/11 * x = 33/16
x = 33/16 * 11/21
x = 121/128
4 2/9 * x + 3 5/14 = 6 11/21
4 2/9 * x = 6 11/21 - 3 5/14
4 2/9 * x = 6 22/42 - 3 15/42
4 2/9 * x = 3 7/42
38/9 * x = 3 1/6
38/9 * x = 19/6
x = 19/6 * 9/38
x = 3/4
x = 0,75
11/18 - 14/27 * x = 5/12
14/27 * x = 11/18 - 5/12
14/27 * x = 22/36 - 15/36
14/27 * x = 7/36
x = 7/36 * 27/14
x = 3/8
x = 0,375
1/3 * x + 1/4 * x + 1/5 * x = 1 19/75
20/60 * x + 15/60 * x + 12/60 * x = 94/75
77/60 * x = 94/75
x = 94/75 * 60/77
x = 376/385
4 1/2 : x + 1 3/4 = 3 19/28
4 1/2 : x = 3 19/28 - 1 3/4
4 1/2 : x = 3 19/28 - 1 21/28
9/2 : x = 2 47/28 - 1 21/28
9/2 : x = 1 26/28
9/2 : x = 1 13/14
9/2 : x = 27/14
x = 9/2 * 14/27
x = 7/3
x = 2 1/3
3 2/3 : (x - 2 4/15) = 3 5/13
11/3 : (x - 2 4/15) = 44/13
x - 2 4/15 = 11/3 * 13/44
x - 2 4/15 = 13/12
x = 13/12 + 2 4/15
x = 1 1/12 + 2 4/15
x = 1 5/60 + 2 16/60
x = 3 21/60
x = 3 7/20
x = 3,35
Пошаговое объяснение:
Я точно не знаю правильно это